Determining the mean difference in central corneal thickness measured by applanation ultrasound and oculus Wavelight Occulyzer II - memon, Dr Ronak afza; Shakir, Dr munira; Wasim, Dr Sahira (Pakistan Journal of Ophthalmology, 2021)
Abstract Objective: The objective is to determine the mean difference of central corneal thickness measurements by using ultrasound pachymeter and oculus Wavelight Occulyzer II. Patients & Methods: This prospective cross-sectional comparative study was conducted at Department of Ophthalmology, Liaquat National Hospital, Karachi for 6 months duration, after the approval from ethical committee. Patients were included in our study on the basis of inclusion & exclusion criteria. Central corneal thickness measurements was taken by using ultrasound pachymeter & oculus Wavelight Occulyzer II. All the data was collected by single researcher. The results were plotted, compared & analyzed. Results: 130 patients attending ophthalmology department and fulfilling the inclusion criteria were assessed. One eye of each patient was measured (65 were right eye and 65 were left eye). 73(56.2%) were male and 57(43.8%) were females. Mean age of these patients was 33.9 ±8.9 years. The mean ± SD thinnest oculus Wavelight Occulyzer II measurement was 538.61±23.46 ?m and ranged between 476.0 and 619.0 ?m whereas the mean thinnest ultrasound pachymeter measurement was 535.1±21.816?m and ranged between 482 and 601 ?m. There was highly significant correlation of central corneal thickness between both the instruments. (r=0.96, p<0.001) Conclusion: According to the results of our study there is a highly correlation of central corneal thickness was found between the readings obtained from both UP and oculus Wavelight Occulyzer II. So we concluded that oculus Wavelight Occulyzer II can be used as an alternative technique to ultrasound pachymetry while assessing CCT in clinical settings to decrease the risk of procedure associated problems with UP like epithelial trauma and infection, to decrease the frequent use of topical anesthetic agents, for early detection and management of glaucoma & in anxious patients also. Keywords: Central corneal thickness, ultrasound pachymeter, oculus Wavelight Occulyzer II